Implementasi Sistem Sensor Dan Aktuator Real Time Pada Tanaman Jamur - M. Sandy Anshori; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Before the advent of RTOS, embedded systems using primitive interrupt to initiate a process of multitasking. Hiking the cultivation of Oyster Mushrooms or other mushrooms, we require preparatory steps include setting up the exact location or suitable for placing House mushrooms, prepare the mushroom seeds, prepare a sterile growing media and other means of treatment. To implement an RTOS in fungi and plant watering monitor automatically using the FreeRTOS. FreeRTOS is applied using three Task in all nodes the actuator sensor & first serve which monitor temperature and humidity, the second monitor large discharge of water and the water flow, turn on the water pump automatically, and the last function sends data to the gateway node. After all the Task was implemented, node gateway will receive data from the sensors and actuators & node sends the data to the webserver. Data is sent in the form of readings of temperature, humidity, large discharge of water, lots of water flow, and the State of the water pumps are turned on or not. When data is received to the webserver, data is entered into a database and displayed via a web page named